Immunization With Lipopolysaccharide-Activated Dendritic Cells Generates a Specific CD8+ T Cell Response That Confers Partial Protection Against Infection With Trypanosoma cruzi - Biscari, Lucía; Kaufman, Cintia Daniela; Farré, Cecilia; Huhn, Victoria; Pacini, María Florencia; Balbi, Camila Bulfoni; Gómez, Karina Andrea; Pérez, Ana Rosa; Alloatti, Andrés (Frontiers in Cellular and Infection Microbiology, 2022)
Lipopolysaccharide (LPS) induces the activation of dendritic cells (DCs) throughout the engagement of toll-like receptor 4. LPS-activated DCs show increased capacity to process and present pathogen-derived antigens to activate naïve T cells. DCs-based vaccines have been successfully used to treat some cancer types, and lately transferred to the field of infectious diseases, in particular against HIV. However, there is no vaccine or DC therapy for any parasitic disease that is currently available. The immune response against Trypanosoma cruzi substantially relies on T cells, and both CD4+ and CD8+ T lymphocytes are required to control parasite growth. Here, we develop a vaccination strategy based on DCs derived from bone marrow, activated with LPS and loaded with TsKb20, an immunodominant epitope of the trans-sialidase family of proteins. We extensively characterized the CD8+ T cell response generated after immunization and compared three different readouts: a tetramer staining, ELISpot and Activation-Induced Marker (AIM) assays. To our knowledge, this work shows for the first time a proper set of T cell markers to evaluate specific CD8+ T cell responses in mice. We also show that our immunization scheme confers protection against T. cruzi, augmenting survival and reducing parasite burden in female but not male mice. We conclude that the immunization with LPS-activated DCs has the potential to prime significant CD8+ T cell responses in C57BL/6 mice independently of the sex, but this response will only be effective in female, possibly due to mice sexual dimorphisms in the response generated against T. cruzi.